Verfahren zur Beurteilung der Schadensumfangs- und Zustandsentwicklung vorgespannter Brückenbauwerke - Kirpal, Eric (Karlsruher Reihe Massivbau, Baustofftechnologie, Materialprüfung, 2021)
The knowledge of damage processes and their influence on the development of the system´s response is of great significance for the maintenance of infrastructure constructions. By means of computer aided recalculations, the effects of corrosive, fatigue relevant and interacting effects on structures can be estimated and remaining service lifes can be predicted through comparison of simulated system responses with normatively determined limit states.